2020
DOI: 10.1177/1758835920978110
|View full text |Cite
|
Sign up to set email alerts
|

Building the case for the calcitonin receptor as a viable target for the treatment of glioblastoma

Abstract: Researchers are actively seeking novel targeted therapies for the brain tumour glioblastoma (GBM) as the mean survival is less than 15 months. Here we discuss the proposal that the calcitonin receptor (CT Receptor), expressed in 76–86% of patient biopsies, is expressed by both malignant glioma cells and putative glioma stem cells (GSCs), and therefore represents a potential therapeutic target. Forty-two per cent (42%) of high-grade glioma (HGG; representative of GSCs) cell lines express CT Receptor protein. CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 132 publications
(262 reference statements)
0
15
0
Order By: Relevance
“…As possible reasons for inactivation were AS splicing, a switch to the CT Receptor b isoform or other mutations [ 159 ]. It was concluded that targeting the CT Receptor by immunotoxin is expected to provide an additional “knife”, in combination with traditional therapy of GBM [ 160 ]. The Glycogen Synthase Kinase-3 gene (GSK3) is responsible for a regulatory Ser/Thr protein kinase that exists in two distinct isoforms, GSK3α and GSK3β [ 161 ].…”
Section: Gliomamentioning
confidence: 99%
“…As possible reasons for inactivation were AS splicing, a switch to the CT Receptor b isoform or other mutations [ 159 ]. It was concluded that targeting the CT Receptor by immunotoxin is expected to provide an additional “knife”, in combination with traditional therapy of GBM [ 160 ]. The Glycogen Synthase Kinase-3 gene (GSK3) is responsible for a regulatory Ser/Thr protein kinase that exists in two distinct isoforms, GSK3α and GSK3β [ 161 ].…”
Section: Gliomamentioning
confidence: 99%
“…The tumour hierarchy or architecture includes regions of necrosis and oedema [ 5 ], where the blood–brain barrier is compromised and antibodies are able to penetrate [ 6 ] pro-inflammatory micro-environments with cellular infiltrates and vascular-like structures (vascular mimicry [ 7 ]) with proliferative domains, which are located primarily towards the tumour periphery. Within these latter hyperplastic structures, pericyte precursors and endothelial cells share the same genetic modifications as glioma stem-like cells (GSC), supporting plasticity with regard to differentiation lineages and the existence of dominant GSC clones [ 8 ].…”
Section: Tumour Hierarchy Of Glioblastomamentioning
confidence: 99%
“…CT Receptors are widely expressed through the lifecycle of organisms, in several physiological conditions and diseases, including several cancers such as GBM and prostate cancer [ 5 , 36 ]. At least two different isoforms (insert-negative CT a Receptor and insert-positive CT b Receptor) have been identified in mammals.…”
Section: Expression Of Calcitonin (Ct) Receptor a G Protein-coupled Receptor In Hgg Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations